The importance of environmental licensing for sustainable rural development - Grisa, Jaqueline Gomes Demarchi; Grisa, Kleitson Telmo; Borstel Roesler, Marli Renate von; Feiden, Armin; Hahn, Keitilanger Grisa; Grandi, Adriana Maria de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Environmental licensing can be considered a management tool for organizations, which must be carried out according to norms and principles in order to make it a tool capable of monitoring whether the property is in compliance with the current environmental legislation. It must be performed at appropriate intervals and carefully analyzed to intensify the objectives, always seeking improvements of the productive processes in order to minimize environmental damage. Thus, this article aims to analyze the importance of environmental licensing for sustainable rural development. The method used for this study was the bibliographical research, where several bibliographic sources will be used, to give theoretical foundation to the research. Thus, the article will demonstrate the phases of environmental licensing as well as the themes related to sustainable rural development, in order to identify how environmental licensing has a great relation with sustainability, since it conditions limits and restrictions for the development of potentially polluting activities that, in practice, take into account and is based on the importance of not attacking the environment.